Implementasi Kurikulum 2013 pada Mata Pelajaran Aqidah Akhlak di SDIT BIN BAZ Kabupaten Rejang Lebong - Ririn Wahyuni; Hendra Harmi; Irwan Fathurrochman; Endang Endang (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2020)
This research is a field research using a qualitative descriptive method. The results of this study can be concluded that the implementation of the 2013 curriculum in the Aqidah Akhlak Subject at SDIT BIN BAZ has been running well even though it is not yet at the maximum stage, the desert council has followed the provisions in accordance with the 2013 curriculum as a guide in teaching and learning activities, but the Implementation Plan Learning still follows the regulations from Permendikud Number 22 concerning Basic and Secondary Education Process Standards and has not followed Circular Number 14 of 2019 concerning Simplification of the Learning Implementation Plan. The difficulty in implementing the 2013 curriculum in the subject of Aqidah Akhlak is more due to the lack of facilities and infrastructure to assist in the teaching and learning process and besides that the teacher council has difficulty in assessing students using the 2013 curriculum because there are many points or aspects that need to be considered for conducting assessments and towards students.